PENGARUH JARAK TERHADAP KUALITAS GAMBAR DALAM PENGIRIMAN CITRA DIGITAL MELALUI JARINGAN WIRELESS PADA KAMERA LS Y201 - Hidayat, Zhulfa Arif; Dermawan, Denny; Retnowati, Nurcahyani Dewi (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2013)
Digital image was needed us a medium of information that can be transmitted by cable or wireless media. To obtain digital images must use a tool such as a camera. Users can use the camera to get a digital image with the remote sensing method on an object in a particular place. In the daily activities, users can take advantages of the digital image (pictures or video) that are useful for media documentation, monitoring system in somewhere and others. The design of this tool using LS_Y201camera to capture a digital image and wireless as a data transmission media. In this case a wireless media use Ultra High Frequency transmitter and receiver that support for remote sensing. Users run the tool through an application that is connected with a wireless media. This application is designed byDelphi7. Applications and wireless camera was made for simulation media of remote sensing and monitoring system in the blank spot area. The test result of applications and tools that use the Ultra High Frequency (wireless), can be viewed from a computer interface. In this case, the signal strength ofthe transmitter greatly affect the maximum distance that can be taken to make capture process. The test results are as follows: the best results at a distance of 10 meters = 011110102 (12210); distance of 20 meters = 011100112 (11510); distance of 30 meters = 011110102 (12210); distance of 40 meters =011011112 (11110); distance of 50 meters = 011100102 (11410). So the best distance to digital images transmission through a wireless networks are at a distance of 40 meters.